Nanostructured ZnO-CQD hybrid heterostructure nanocomposites: synergistic engineering for sustainable design, functional properties, and high-performance applications - Mishra, Raghvendra Kumar; Chianella, Iva; Sarkar, Jayati; Nezhad, Hamed Yazdani; Goel, Saurav (Wiley, 2024)
Hybrid nanocomposites integrating nanostructured zinc oxide (ZnO) and carbon quantum dots (CQDs) with designed heterostructures possess exceptional optical and electronic properties. These properties hold immense potential for advancements across diverse scientific and technological fields. This review article investigates the synthesis, properties, and applications of ZnO-CQD heterostructure nanocomposites. Recent breakthroughs in fabrication methods are examined, including hydrothermal, microwave-assisted, and eco-friendly techniques. Key preparation methods such as sol-gel, co-precipitation, and electrochemical deposition are discussed, emphasizing their role in controlling heterostructure formation. This review analyses the impact of heterostructures on optical and electronic properties, such as fluorescence, photoluminescence, and photocatalytic activity. Synergistic interactions between ZnO and CQDs within heterostructures are highlighted, demonstrating how they lead to substantial performance improvements. Applications of ZnO-CQD heterostructures span solar cells, LEDs, photodetectors, water purification, antimicrobial treatments, gas sensing, catalysis, biomedical imaging, drug delivery, environmental sensing, and energy storage. Insights are provided into refining synthesis methods, enhancing characterisation techniques, and broadening the application landscape. Challenges like stability are addressed, along with strategies for optimised performance and practical implementation.
Keywords: Nanostructured Zinc Oxide (ZnO); Carbon Quantum Dots (CQDs); Heterostructures; Hybrid Nanocomposites; Sustainability